Clinical features of parainfluenza infections among young children hospitalized for acute respiratory illness in Amman, Jordan - Howard, Leigh M.; Rankin, Danielle A.; Spieker, Andrew J.; Gu, Wenying; Haddadin, Zaid; Probst, Varvara; Rahman, Herdi; McHenry, Rendie; Pulido, Claudia Guevara; Williams, John V.; Faouri, Samir; Shehabi, Asem; et al. (BMC infectious diseases, 2021)
Background Parainfluenza virus (PIV) is a leading cause of acute respiratory illness (ARI) in children. However, few studies have characterized the clinical features and outcomes associated with PIV infections among young children in the Middle East. Methods We conducted hospital-based surveillance for ARI among children < 2 years of age in a large referral hospital in Amman, Jordan. We systematically collected clinical data and respiratory specimens for pathogen detection using reverse transcription polymerase chain reaction. We compared clinical features of PIV-associated ARI among individual serotypes 1, 2, 3, and 4 and among PIV infections compared with other viral ARI and ARI with no virus detected. We also compared the odds of supplemental oxygen use using logistic regression. Results PIV was detected in 221/3168 (7.0%) children hospitalized with ARI. PIV-3 was the most commonly detected serotype (125/221; 57%). Individual clinical features of PIV infections varied little by individual serotype, although admission diagnosis of ‘croup’ was only associated with PIV-1 and PIV-2. Children with PIV-associated ARI had lower frequency of cough (71% vs 83%; p < 0.001) and wheezing (53% vs 60% p < 0.001) than children with ARI associated with other viruses. We did not find a significant difference in supplemental oxygen use between children with PIV-associated infections (adjusted odds ratio [aOR] 1.12, 95% CI 0.66–1.89, p = 0.68) and infections in which no virus was detected. Conclusions PIV is frequently associated with ARI requiring hospitalization in young Jordanian children. Substantial overlap in clinical features may preclude distinguishing PIV infections from other viral infections at presentation.